2018
DOI: 10.12659/msm.906625
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study to Compare Five Induction Chemotherapy Regimens Prior to Radiotherapy in the Reduction of Regional Lymph Node Size in Patients with Nasopharyngeal Carcinoma

Abstract: BackgroundCombined chemotherapy and radiation therapy are used to treat nasopharyngeal carcinoma (NPC). Previous studies have shown that induction chemotherapy, given before radiotherapy, is beneficial in patients with local lymph node metastases. The aim of this study was to evaluate regional lymph node size in patients with NPC and the efficacy of five induction chemotherapy regimens given before radiotherapy.Material/MethodsBetween December 2007 and June 2011, 190 patients were included in this study, who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…Nasopharyngeal cancer is a common form of neck and head cancer [10]. The treatment of nasopharyngeal carcinoma is limited by early metastasis and the adverse effects of available chemotherapeutic agents [11]. Moreover, development of multi-drug resistance in nasopharyngeal cancer patients makes it challenging to treat [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Nasopharyngeal cancer is a common form of neck and head cancer [10]. The treatment of nasopharyngeal carcinoma is limited by early metastasis and the adverse effects of available chemotherapeutic agents [11]. Moreover, development of multi-drug resistance in nasopharyngeal cancer patients makes it challenging to treat [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…One report [16] demonstrated that the TP regimen may be sufficient for patients receiving a CCD ≥ 200 mg/m 2 , while TPF may be superior to TP and PF for patients receiving a CCD < [36], the TPF regimen yielded better long-term survival for patients with locoregionally advanced NPC in comparison with the PF regimen. In another study [37], TPF showed an improved early response of lymph node size reduction in comparison with the PF and TP regimens. These findings support the results of the present study, in which IC with TPF showed the best short-term tumor response and provided survival benefits compared with those of TP in all cases of locally advanced nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 90%
“…There is increasing evidence that IC can facilitate eradication of micro-metastatic lesions and reduce the risk of distant metastasis [79], so IC is being used widely in clinical settings. Based on studies that have established its superiority over the standard PF regimen for lowering the prevalence of distant metastasis and improving OS prevalence, TPF has emerged as the effective IC regimen [1012].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that taxanes, cisplatin and 5-fluorouracil (TPF) is the effective IC regimen for reducing the risk of treatment failure and improving overall survival (OS) in patients with high risk NPC [1012]. In comparison with the standard cisplatin and fluorouracil (PF) regimen, regimens involving taxanes (microtubule-stabilizing drugs) have been used widely for the treatment of different types of malignancies for decades [13].…”
Section: Introductionmentioning
confidence: 99%